QT dispersion is not related to infarct size or inducibility in patients with coronary artery disease and life threatening ventricular arrhythmias. Issue 5 (1st May 1999) - De Sutter, J; Tavernier, R; Van de Wiele, C; De Backer, J; Kazmierczak, J; De Backer, G; Dierckx, R; Jordaens, L
Abstract : OBJECTIVE: To relate QT parameters to infarct size and inducibility during electrophysiological studies. DESIGN: Analysis of a prospective register. SETTING: University hospital. PATIENTS: 64 patients with coronary artery disease and documented life threatening ventricular arrhythmias. INTERVENTIONS: Measurements of QT-max, QTc-max, and QT dispersion (QT-d) on a simultaneous 12 lead ECG (50 mm/s). Estimation of myocardial infarct size with radionuclide left ventricular ejection fraction (LVEF), echocardiography (left ventricular end diastolic diameter, LVEDD), and a defect score based on a quantitative stress redistribution 201-thallium perfusion study. Electrophysiological study to assess inducibility. RESULTS: Mean (SD) QT parameters were: QT-max 440 (50) ms, QTc-max 475 (46) ms, and QT-d 47 (20) ms. Mean (SD) estimates of infarct size were: LVEF 34 (13)%, LVEDD 61 (9) mm, and defect score 18 (11). There was no significant correlation between any index of infarct size and QT parameters. QT parameters were not significantly different between patients with inducible (n = 57) and non-inducible arrhythmias (n = 7) (QT-max: 416 (30) v 443 (51) ms, p = 0.18; QTc-max 485 (34) v 473 (47) ms, p = 0.34; QT-d 47 (12) v 47 (21) ms, p = 0.73). Non-inducible patients had a significant lower defect score: 8 (9) v 19 (11), p = 0.02, but comparable LVEF: 38 (12)% v 34 (12)%, p = 0.58, and LVEDD: 54 (10) v 61 (8) mm, p = 0.13. CONCLUSIONS: QT parameters are not influenced by infarct size and do not predict inducibility during electrophysiological study in patients with coronary artery disease and malignant ventricular arrhythmias. In contrast, the amount of scar tissue determined by perfusion imaging is strongly correlated with inducibility.